Analysis of questionnaire data with R - Falissard, Bruno (Boca Raton, FL : CRC Press, 2012)
This book deals with questionnaire data, that is, with responses that human beings have given to a series of standardized closed questions.
Includes bibliographical references and index.
rua 27/08/13
Loans
Keywords: Questionnaires -- Data processing; R (Computer program language)